Biofunctionalized Capillary Flow Channel Platform Integrated with 3D Nanostructured Matrix to Capture Circulating Tumor Cells. Issue 4 (18th January 2017) - Banerjee, Shashwat S.; Khutale, Ganesh V.; Khobragade, Vrushali; Kale, Narendra R.; Pore, Milind; Chate, Govind P.; Jalota‐Badhwar, Archana; Dongare, Manoj; Khandare, Jayant J.
Abstract : Circulating tumor cells (CTCs) from peripheral blood account genetic information for cancer diagnosis and overall disease monitoring. Analysis of "liquid biopsy" holds immense promise as it may lead to new approaches for cancer treatment. The study reports effective and continuous flow microchannel system for isolating CTCs using transferrin conjugated 3D matrix synthesized by crosslinking polyethylene glycol‐Fe3 O4 nanostructures for rapid and efficient capturing of CTCs. The platform provides option of using multiple microchannel units in series that can influence higher cell‐capture efficiency due to increasing cell‐substrate contact frequency. CTCs are captured with high efficiency even at low concentration of target cells ( 90% at 25 cells per mL blood). Furthermore, the study demonstrates that the cell‐capture performance is influenced by topographic interactions between nanostructure based matrix and cancer cells of interest. In addition, this study demonstrates the "proof of concept" using 3D microchannel system having capacity of simultaneously capturing and permanently eliminating CTCs from peripheral blood samples. Further, the study evaluates clinical samples of colon and breast cancer patients for rapid isolation of CTCs. Conclusively, the present platform demonstrates inordinate capacity for cancer cell sorting, biological studies of CTCs, and cancer metastasis, potentially benefiting the real time liquid biopsy and early prognosis of cancer. Abstract : A platform for capture of circulating tumor cells and their elimination ex vivo from cancer patients is demonstrated by utilizing a nanostructure based 3D matrix anchored microchannel system. Synergistic effects of enhanced cell–substrate contact frequency as well as ligand–receptor recognition and nanostructure amplification enable a highly efficient and selective capture of cancer cells.